Opinions of Psychiatrists and Emergency Medicine Physicians on the Crime of Healthcare Professionals Not Reporting the Crime Regarding Violence Against Women: Situation Assessment and Evaluations - Yılmaz Karaman, İmran Gökçen; Oktar, Seyhan; Köse, Cansu; Çanakçı, Mustafa Emin; Taşkın, Ozan Ercan (The Bulletin of Legal Medicine, 2024)
Objective: Article 280 of the Turkish Penal Code (TPC) concerns healthcare professionals reporting crimes. Psychiatrists and emergency physicians who frequently encounter patients who have been exposed to violence against women (VAW) are faced with a dilemma when the patient does not want judicial notification.Methods: 138 psychiatrists and 70 emergency medicine physicians participated in the research. In the online survey, participants were asked about their level of knowledge, their attitudes towards VAW, and their experiences with VAW cases. Trends in making judicial notifications and keeping medical records were examined based on physical violence (PV) and sexual violence (SV) case reports.Results: Regarding the case examples, physicians' tendencies to keep medical records and make judicial notifications differ for PV and SV. Emergency medicine physicians are more likely to make judicial notifications in VAW cases than psychiatrists (each p
Keywords: physicians; forensic medicine; forensic psychiatry; violence against women; gender-based violence; exposure to violence